Analysis of the level of knowledge of disaster preparedness attitudes in dealing with the Gamalama volcano disaster among students in senior high schools in the city of Ternate - Abdullah Irwan; Maryani Enok; Ningrum Epon (E3S Web of Conferences)
Natural disasters in Indonesia have been increasing annually, encompassing both geological and hydrometeorological events. One of the recurring natural disasters in Ternate City is the volcanic eruption of Gamalama Volcano. The Gamalama Volcano eruption has direct and indirect dangers for the community, particularly to high school students. The research aims are 1) to determine the knowledge and attitude of disaster preparedness in facing the Gamalama volcano eruption, and 2) to determine the influence of knowledge of disaster preparedness attitudes in dealing with volcanoes on students. This research uses a quantitative descriptive method with a cross-sectional approach and data collection techniques with purposive sampling. The instrument used was a questionnaire sheet on Google form. With a sample size of 150 students, the data analysis techniques are descriptive percentages and simple regression analysis. The research findings show that students’ overall disaster knowledge is in the “good” category. The results of the simple linear regression analysis indicate a significant positive relationship between disaster knowledge and students’ preparedness attitudes. It is essential to enhance disaster-related knowledge in schools located in areas vulnerable to the Gamalama Volcano eruption through formal education, ensuring that students are better prepared to respond effectively during disasters.